Removal and Repositioning of Intracorneal Ring Segments: Improving Corneal Topography and Clinical Outcomes in Keratoconus and Ectasia. Issue 2 (1st December 2016) - Chan, Kahei; Hersh, Peter S.
Abstract : Purpose: To evaluate the efficacy of removal and relocation of intracorneal ring segments for improving outcomes in treatment of keratoconus and corneal ectasia. Methods: This is a retrospective case series conducted at a cornea and refractive surgery subspecialty practice setting. Patients with previous insertion of 2 intracorneal ring segments underwent surgical removal and repositioning of segments because of unsatisfactory visual and topographic outcomes. The principal outcomes included uncorrected and corrected visual acuities, manifest refraction, topography-derived maximum keratometry (Kmax), inferior–superior topography power difference (I − S), and higher-order aberration profile derived from wavefront analysis. Results: Three patients are presented in this case series. Uncorrected visual acuity improved in all eyes by an average of 2.75 lines. Corrected visual acuity improved in 2 eyes and remained unchanged in 1 eye. Refractive astigmatism decreased in all patients by an average of 2.50 D. Kmax decreased by an average of 1.43 D. All patients had improvement in the I − S value with a mean decrease of 5.13 D. Conclusions: Topography-guided repositioning and/or replacement of corneal ring segments can result in improved topographic, optical, and visual outcomes in patients in whom the initial result is suboptimal. In these cases, a single segment repositioned beneath the cone resulted in an improved outcome. Analysis of corneal topography can guide the surgeon in treatment planning and can suggest patients in whom such an effort will be rewarded with better results.